Participatory communion: an ecclesiological inquiry on lay participation in the local church based on the documents of the FABC (1970 - 2006) - Thainese, Alphonse (Indian Society for Promoting Christian Knowledge, 2008)
Study conducted in Andhra Pradesh, India